Nanoscale Engineering of Optical Strong Coupling inside Metals. Issue 2 (20th December 2022) - Assadillayev, Artyom; Faniayeu, Ihar; Dmitriev, Alexandre; Raza, Søren
Abstract: Optical polaritons appear when a material excitation strongly couples to an optical mode. Such strong coupling between molecular transitions and optical cavities results in far‐reaching opportunities in modifying fundamental properties of chemical matter. More recently an exciting prospect of self‐coupled polaritons has emerged by matter sustaining the optical mode with its geometry. Here, it is shown how strong coupling of the interband transition and surface plasmons can be engineered in nickel at the nanoscale to realize self‐coupled plasmon–interband polaritons inside metals. Using electron energy‐loss spectroscopy, it is demonstrated that in nickel thin films and nanoantennas the propagation and radiation losses result in a broadening of the plasmon linewidth and a transition from strong to weak coupling. Further, higher‐order plasmon resonances couple to the interband transition, and the multipolar‐coupled states acquire the field profile of the plasmon. The results provide a fundamental understanding of plasmon–interband coupling in metals and establish the base for the design of photocatalytic and magneto‐optical nanosystems. Abstract : Self‐coupled interband–plasmon resonances in nickel nanostructures are engineered from the strong to the weak coupling regime. The transition between strong and weak coupling is experimentally demonstrated using electron energy‐loss spectroscopy (EELS) by varying the thickness of nickel films and the size of colloidal nickel nanoparticles.